(3GdEjYGH aj TQM GdYHGHs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s
(3ChdgG (B:s
(3fMeOc Gddge Cf TQMJ UOQh CbhGe HGdabg hbQHJge ef MVQJc hSbjJge ef YHGH ajV aVdcs
(3BNQgG (B:s
(3ceG bGd GdQhjGfj hZjQg Cj ajg fhY TOI deG jCJj Cfg jfHZj YOe GdEeYGf aj GdGSJHQGO hCfg jhQK VQQGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 46s
(3eYLe GdeDdajf (B1 / 733s
(3TPQGJ GdPgH (B8 / 134 - 136s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdTGaYjs